2000
DOI: 10.1139/f00-084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unstable aluminium chemistry on Arctic char (Salvelinus alpinus)

Abstract: Arctic char (Salvelinus alpinus) were exposed to a non-steady-state Al-rich medium (pH 5.8, total Al 480 mg·L -1 , total organic C 3.0 mg C·L -1 , Ca 2+ 2.9 mg·L -1 , temperature 7.5°C). An Al-poor medium (pH 5.2 and 5.8, total Al 99 mg·L -1 , total organic C 3.0 mg C·L -1 , Ca 2+ 2.9 mg·L -1 , temperature 8.0°C) acted as control. The Al-rich medium was acutely toxic to the Arctic char. Total mortality (percent) and mortality rate (LT 50 ) were highest in fish exposed to the Al-rich medium immediately after mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 37 publications
6
18
1
Order By: Relevance
“…It is well documented that Al-toxicity in various aquatic biota depends on changes in water physico-chemical conditions, rather than the presence or the concentration of a certain aluminium species [ 1 , 3 , 8 11 ]. Accordingly, it has been demonstrated that a non-steady state Al-chemistry often predominate in natural environments [ 12 15 ], in which monomeric Al-forms are transformed to polymeric Al-forms, may dictate the Al-toxicity [ 16 ]. When Al-solubility decreases as pH is elevated in an acidic water body, the toxicity to fish increases because aluminium starts to polymerise, and subsequently accumulates on the gill surface [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that Al-toxicity in various aquatic biota depends on changes in water physico-chemical conditions, rather than the presence or the concentration of a certain aluminium species [ 1 , 3 , 8 11 ]. Accordingly, it has been demonstrated that a non-steady state Al-chemistry often predominate in natural environments [ 12 15 ], in which monomeric Al-forms are transformed to polymeric Al-forms, may dictate the Al-toxicity [ 16 ]. When Al-solubility decreases as pH is elevated in an acidic water body, the toxicity to fish increases because aluminium starts to polymerise, and subsequently accumulates on the gill surface [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been demonstrated that a non-steady state Al-chemistry often predominate in natural environments [ 12 15 ], in which monomeric Al-forms are transformed to polymeric Al-forms, may dictate the Al-toxicity [ 16 ]. When Al-solubility decreases as pH is elevated in an acidic water body, the toxicity to fish increases because aluminium starts to polymerise, and subsequently accumulates on the gill surface [ 10 , 16 ]. The primary effect of Al-polymerisation and precipitation or accumulation on the fish gill surface has been suggested to be hypoxia [ 10 11 , 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In combination with a lowered dissolved O 2 -concentration, such accumulation might lead to hypoxia. Accordingly, it has been suggested that hypoxia is of major importance for the acute effect of acidic aluminium rich water, especially under unstable physico-chemical conditions (Neville 1985;Poléo et al 1994Poléo et al , 1995Witters et al 1996;Poléo & Bjerkely 2000). The idea that hypoxia is of importance, is also indicated by the results showing that the larger fish had the higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, organic Hg (e.g. methyl-mercury) is more likely to accumulate and cause toxic effects to fish than the inorganic form (Boudou and Ribeyre, 1985), monomeric inorganic Al is more toxic than more polymerised forms, due to the greater capacity of monomeric inorganic Al to bind to gill surfaces and damage gill function (Poléo and Bjerkely, 2000;Alstad et al, 2005), Fe 2+ has greater toxicity to aquatic organisms than the Fe 3+ form, and at high concentrations, causes oxidative damage to cells and organs (Bury and Grosell, 2003;Chen et al, 2011).…”
Section: Bioindicators Of Pollutionmentioning
confidence: 99%